Risk Analysis of Business of Sumbawa Forest Honey in Sumbawa Regency - Nila Wijayanti; Bulan Fiola Auliyasya; Siti Nurwahidah; Syahdi Mastar; Alia Wartiningsih (Journal of Global Sustainable Agriculture, 2026)
The risks of forest honey production are greatly influenced by natural factors such as weather, temperature, drought, and flooding. In addition to natural factors, risks can also arise from marketing activities. The purpose of this study was to identify the risks and risk levels of the Sambava Honey trading business in Sumbawa Regency. The study was conducted in February 2025 at UD. Sambava Honey Sumbawa. The sample was selected using purposive sampling. The sample consisted of the forest honey business owners of UD. Sambava Honey. Data analysis in identifying risks used a fishbone diagram (Fishbone Matrix), and for risk levels used the Matrix Impact Factor. The results of the study found that product risks in the Sambava Honey trading business include honey availability (stock and delays in supply); honey quality (water content is not always good >22%, weather affects honey quality, place and length of storage time); and packaging (damaged bottles and packaging labels). Market risks include consumer behavior (consumer complaints about convex packaging and constantly changing prices); product selling prices (supply prices increase, shipping costs increase, and honey prices fluctuate); competitors (the presence of cultivated honey and other brands of honey); and marketing (obstacles in promotion and sales). Partnership risks consist of cooperation partners (obstacles with partners in providing and shipping honey supplies, obstacles in shipping, and obstacles with partners in procuring packaging and labels); and cooperation contracts (collaboration contracts are suddenly terminated unilaterally, and the cooperation contract is unclear). There are no high levels of risk in the Sambava Honey forest honey business. Fourteen risks are classified as low risk, and seven are classified as medium risk.